The Effect of Flash-Based Learning Media on Students’ Achievement in Learning Atomic Structure in Kenyan Senior High Schools - Jairus Bulimo Khamali; Helen Omondi Mondoh (Journal of Chemical Learning Innovation, 2025)
Purpose of the study: This study aims to investigate the effect of Flash-based learning media on students’ learning achievement in chemistry, particularly on the topic of atomic structure, in Kenyan senior high schools. Methodology: The study employed a quasi-experimental research design using a pretest–posttest control group approach. The participants consisted of 84 Grade 10 students from a public senior high school in Kenya, divided into an experimental group and a control group. The experimental group was taught using Flash-based learning media featuring animated visualizations of atomic models, subatomic particles, and electron configurations, while the control group received conventional instruction. Data were collected using a validated chemistry achievement test and analyzed using an independent samples t-test. Main Findings: The results showed that students who learned using Flash-based media achieved significantly higher posttest scores than those taught using conventional methods. The statistical analysis revealed a significant difference between the experimental and control groups (t = 3.24, p < 0.05), indicating that Flash-based learning media had a positive effect on students’ achievement in learning atomic structure. Novelty/Originality of this study: This study provides empirical evidence on the effectiveness of Flash-based learning media in chemistry education within the Kenyan context, which remains underexplored. The findings highlight the potential of interactive multimedia to enhance students’ conceptual understanding of abstract chemistry topics and support the integration of digital learning media in secondary science education in developing countries.